An Engineering Solution to Improve Post-Earthquake Fire Resistance in Important Reinforced Concrete Structures. Issue 7 (July 2014) - Behnam, Behrouz; Ronagh, Hamid
An investigation based on sequential analysis is performed here on the Immediate Occupancy performance level of important structures designed to the ACI 318–08 code after they are subjected to earthquake level with PGA of 0.30 g. This is followed by a fire analysis of the damaged structure, from which the time it takes for the damaged structure to collapse is calculated. As a benchmark, the fire analysis is also performed for the undamaged structure and before the occurrence of earthquake. The results indicate that the vulnerability of structures increases when a previously damaged structure is exposed to fire. A post-earthquake fire (PEF) factor as a function of the required fire resistance time is then proposed to improve the fire resistance of important buildings subjected to PEF. Whilst the investigation is for a certain class of structures (important building, intermediate reinforced structure, 5 stories) and the results can only be expected to be applicable to the cases investigated, it is hoped that it paves the way for further research into this important phenomenon.